The Relationship between Husbands’ Knowledge and Support among Working Pregnant Women in Stunting Prevention at RSIA Yasmin Palangka Raya - Gustin Kurma Wati; Sulastri Sulastri; Eka Listiana; Khairun Nisa; Qodri Aziz (Jurnal Kesehatan dan Kedokteran, 2026)
Maternal nutrition during pregnancy is an important entry point for stunting prevention. In this context, husbands may influence pregnant women’s health behaviors through knowledge and practical support, particularly when pregnant women are employed and face dual role demands. However, evidence regarding whether husbands’ knowledge is reflected in supportive behaviors remains limited in local clinical settings. Objective: This study aimed to examine the relationship between husbands’ knowledge and husbands’ support in the context of stunting prevention at RSIA Yasmin Palangka Raya. Method: This study employed a quantitative descriptive correlational design with a cross-sectional approach. Data were collected from 30 respondents during antenatal care visits using structured questionnaires that assessed husbands’ knowledge regarding pregnancy health and stunting prevention, as well as husbands’ support across emotional, instrumental, and informational dimensions. The association between variables was analyzed using Spearman’s rank correlation with a significance level of p < 0.05. Findings: The results showed that most husbands had good knowledge (93.3%), while husbands’ support was predominantly at a moderate level (83.3%). The correlation between husbands’ knowledge and support was very weak and not statistically significant (r = 0.141; p = 0.458). These findings indicate that higher knowledge does not necessarily translate into stronger practical support for pregnant women. Implications: These findings suggest that stunting-prevention interventions should not only focus on improving husbands’ knowledge but also address practical constraints and sociocultural factors that influence husbands’ involvement in maternal nutrition and pregnancy care. Strengthening family-based support strategies may enhance the effectiveness of maternal and child health programs. Originality: The originality of this study lies in its focus on the gap between husbands’ knowledge and actual supportive behavior in the context of stunting prevention within a local maternal health service setting. This study provides practical evidence that knowledge alone is insufficient to ensure support, thereby contributing to the development of more context-sensitive family-centered interventions.